2006
DOI: 10.1152/ajpheart.00722.2006
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of astrocytes and CO to pial arteriolar dilation to glutamate in newborn pigs

Abstract: Astrocytes can act as intermediaries between neurons and cerebral arterioles to regulate vascular tone in response to neuronal activity. Release of glutamate from presynaptic neurons increases blood flow to match metabolic demands. CO is a gasotransmitter that can be related to neural function and blood flow regulation in the brain. The present study addresses the hypothesis that glutamatergic stimulation promotes perivascular astrocyte CO production and pial arteriolar dilation in the newborn brain. Experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
106
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(114 citation statements)
references
References 59 publications
7
106
1
Order By: Relevance
“…Our previous studies in piglets demonstrated that glutamate stimulates astrocytic CO production in primary-cultured astrocytes and in vivo (24,26,31). We also demonstrated that astrocytes release CO and astrocyte-derived CO causes glutamate-induced pial arteriolar dilation in vivo (24), supporting a regulatory role for astrocytic CO in neurovascular coupling in the newborn brain.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Our previous studies in piglets demonstrated that glutamate stimulates astrocytic CO production in primary-cultured astrocytes and in vivo (24,26,31). We also demonstrated that astrocytes release CO and astrocyte-derived CO causes glutamate-induced pial arteriolar dilation in vivo (24), supporting a regulatory role for astrocytic CO in neurovascular coupling in the newborn brain.…”
supporting
confidence: 53%
“…Functional hyperemia has been investigated extensively, and many astrocyte-derived vasoactive mediators, including ADP (40, 41), ATP (34, 36), epoxyeicosatrienoic acids (1-3), K ϩ (11, 13, 33), and prostacyclin (42), appear to be involved, depending on experimental models. We have shown that carbon monoxide (CO) is another critical regulator of cerebrovascular tone in newborn piglets (19,24,26,31,39).CO dilates newborn pig pial arterioles (22,25). CO causes vasodilation by stimulating Ca 2ϩ sparks and large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channels and by increasing effective coupling between Ca 2ϩ sparks and BK Ca channels in arterial smooth muscle cells (17,18,25,38).…”
mentioning
confidence: 99%
“…2,15,17,19,35 Pial arteriolar dilation to heme, the HO substrate, also involves both endothelial and astrocyte components that express HO-2 and produce vasodilator CO upon stimulation. 2,4,14,17,35 During the delayed postictal period, we observed a dramatic loss of cerebral vascular dilation to astrocyte-dependent vasodilator ADP, and endothelium-astrocyte-dependent stimuli, including glutamate, quisqualate, and heme. These findings, for the first time, show that neonatal seizures cause astrocyte injury leading to loss of astrocyte regulation of cerebral blood flow.…”
Section: Discussionmentioning
confidence: 84%
“…Pial arteriolar dilation to ADP requires the presence of intact and functionally active glia limitans astrocytes. 14,15 Postictal cerebral vascular responses to ADP (10 − 4 mol/L) were greatly reduced compared with the intact control group (Figure 2).…”
Section: Acute Effects Of Enteral Corm-a1 In Systemic and Cerebral CImentioning
confidence: 95%
See 1 more Smart Citation